(untitled) (Journal of Universal Science Research, 2023)
The Republic of Uzbekistan, like many developing countries, faces the challenge of meeting the increasing energy demands of its growing population and expanding economy while simultaneously addressing concerns regarding energy security, environmental sustainability, and economic stability. This article explores the bases of state regulation of energy consumption and the strategies implemented to increase energy efficiency in Uzbekistan.